THE EFFECT OF BONDING AND SURFACE SEALANT APPLICATION ON POSTOPERATIVE SENSITIVITY FROM POSTERIOR COMPOSITES - Neslihan TEKÇE; Mustafa DEMİRCİ; Sultan Aslıhan GÖKTÜRK; Safa TUNCER; Emre ÖZEL; Kanşad PALA; Canan BAYDEMİR (Istanbul University, 2015)
Purpose: The purpose of the study was to evaluate the postoperative sensitivity of posterior Class I composite restoration at short-term, restorated with two different all-in-one self-etch adhesives with or without surface sealant application. Materials and Methods: 44 restorations were inserted in 11 patients who required Class I restorations in their molars. Each patient received 4 restorations, thus four groups were formed; (1) G-Aenial Bond (GC, Japan); (2) Clearfil S3 Bond (Kuraray, Japan); (3) G-Aenial Bond+Fortify Plus (Bisco, USA), (4) Clearfil S3 Bond+Fortify Plus. Sensitivity was evaluated at 24h, 7, 15, and 30 days using cold air, ice, and pressure stimuli using a visual analog scale. Comparisons of continuous variables between the sensitivity evaluations were performed using the Friedman's One-Way Analysis of Variance with repeated measures test (p<0.05). Results: The type of adhesive used and the application of a surface sealant had no significant effects in postoperative sensitivity (p>0.05). The use of Clearfil S3 Bond resulted in almost the same level of postoperative sensitivity as did the use of G-Aenial Bond. The highest sensitivity scores were observed for the surface sealant applied teeth without any statistical significance (p>0.05). Conclusions: Self etch adhesives displayed postoperative sensitivity. The sensitivity scores slightly decreased at the end of 30 days (p>0.05). Surface sealant application did not result in a decrease in sensitivity scores for either dentin adhesives.